Uncertainty principles for the kontorovich‐lebedev transform - Yakubovich, Semyon B. (Mathematical Modelling and Analysis, 2008)
By using classical uncertainty principles for the Fourier transform and composition properties of the Kontorovich‐Lebedev transform, analogs of the Hardy, Beurling, Cowling‐Price, Gelfand‐Shilov and Donoho‐Stark theorems are obtained. First Published Online: 14 Oct 2010